Everyday Life from a Sacral Perspective. Individual Entries in Prayer Books of Intentions as Material for Social Research - Rafał Cekiera (MDPI AG, 2021)
This paper presents the exploratory potential of entries in prayer books of intentions displayed in places of worship and in their online counterparts—virtual boxes of intentions. By reporting the happiness, dramas, and the whole element of human existence, individual prayer intentions are extremely authentic and valuable source materials. Their analysis requires extraordinary ethical sensitivity on the part of the researcher. Based on a review of previous research explorations and my own research, a four-dimensional model of analysis is proposed, consisting of the following areas: axionormative, communitarian, communicative, and ordinary theology. It can be useful for developing analyses of such documents and also allows for comparative research. The text also discusses the limitations associated with such analyses and briefly signals the basic ethical dilemmas and possible directions for further research using prayer entries.